MO569MACROPHAGE PROMOTE VASCULAR CALCIFICATION VIA THE MIGRASOMES/ INTEGRIN Α5Β1 PATHWAY IN CKD. (29th May 2021) - Zhu, Xiaodong; Liu, Yuqiu; Yang, Xin; Fang, Yaping; Zhang, Xiao liang
Abstract: Background and Aims: Patients with chronic kidney disease (CKD) have a predisposition to develop vascular calcification due to dysregulated homeostatic mechanisms. Macrophages can promote vascular calcification by releasing diverse extracellular vehicles including the newly found migrasomes (M-mig). Our previous research had found that M-mig provide nucleating foci for calcific mineral formation and initiating bone mineralization process. However, the specific mechanism by which M-mig influence the formation of vascular calcification remains incompletely understood. Method: To study calcifying M-mig, we exposed M-mig to high Ca/P (Ca/P=3 mmol/L calcium/2 mmol/L phosphate) and/or with LPS for 1, 3, 5, 7 days. The expression of M-mig surface integrin α5β1 was determined by fluorescence staining. To block the M-mig-integrin α5β1 mediated calcification, we modulated the expression of integrin α5 using siRNAs to produce M-mig integrin α5- or using 20 nM ATN-161 (small peptide antagonist of integrin α5β1) or integrin α5 antibody under high Ca/P stimulation. The stray mice artery co-cultivate with M-mig integrin α5- under high level Ca/P. Then the calcifying M-mig were assessed by TEM, Fluo-3 staining and calcium content assay. Results: We discovered that Ca/P-stimulated macrophages released M-mig capable of mineralization. Amorphous calcium phosphate mineral deposit the surface or internal of M-mig. The M-mig exhibited increased Ca/P mineral content, implying aggregate larger calcifying M-mig that develop over time. Significantly, following a 7 days incubation with high level Ca/P, fiber tube and vesicle structure of M-mig showed rupture or fragmentation and the expression of M-mig surface integrin α5β1 increased. Pre-treatment with integrin α5β1 antagonist or block by integrin α5 antibody significantly reduced the calcifying M-mig formation. Further investigation showed that M-mig induced stray mice artery microcalcification while M-mig integrin α5- exhibited a reduce microcalcification. Conclusion: Our finding revealed an association between microcalcification and integrin α5β1 signalling in the fiber tube and vesicle structure of M-mig and provide a new insight into vascular calcification in CKD.